2020
DOI: 10.1039/c9gc03357b
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon embedded with Fe/Ni nano-catalysts derived from bacterial precursor for efficient toluene cracking

Abstract: Highly-dispersed FeNi nano-catalysts embedded in bacterial derived graphitic carbon were successfully synthesized as sustainable and efficient tar cracking catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…2j also clearly demonstrate the presence of all of the elements (K, I, O, C and N). 41 Therefore, these results soundly prove the successful preparation of the co-modified g-CN-KIO 3 . Crucially, the unique K-I-O co-modification may effectively inhibit the recombination of photoinduced charge carriers and thus boost the photocatalytic performance.…”
Section: Feasibility Verification Of K/i/o Co-modificationsupporting
confidence: 54%
“…2j also clearly demonstrate the presence of all of the elements (K, I, O, C and N). 41 Therefore, these results soundly prove the successful preparation of the co-modified g-CN-KIO 3 . Crucially, the unique K-I-O co-modification may effectively inhibit the recombination of photoinduced charge carriers and thus boost the photocatalytic performance.…”
Section: Feasibility Verification Of K/i/o Co-modificationsupporting
confidence: 54%
“…CaO–TiO 2 nano-catalyst was applied in co-transesterification reaction of waste chicken eggshells, glycerol, and glycerol carbonate in a reflux condensation process. The results showed that CaO/TiO 2 provided 99.3% conversion of glycerol with 93.7% of glycerol carbonate yield, it can be used in food, medicine, new energy and other fields [ 215 ]. Steam reforming was applied to convert ethylene glycol over alumina supported Ni-Pt bimetallic catalysts [ 216 ].…”
Section: Advanced Technologies Of Halub Conversion and Managementmentioning
confidence: 99%
“…[22,23,25,84] Carbon material Biomass and coal char Low cost, high specific surface area, porous structure and strong capacity for metal highly dispersion and strong metal-support interaction. [28,34,[85][86][87][88][89][90][91] dant surface acid groups and oxygen-containing functional groups, a relatively low cost andeasy availability. It can effectively adsorb light tar compounds and cooperate with active metals to achieve the removal of biomass tar.…”
Section: Mineral Natural Calcined Olivine and Dolomitesmentioning
confidence: 99%